ANALISIS PEMASARAN CASSIAVERA DENGAN PENDEKATAN STRUCTURE, CONDUCT DAN PERFORMANCE (SCP) DI KABUPATEN KERINCI - Hardiyanti, Wika; Wahyuni, Ira; Rahman, A (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
ABSTRACT Product information dissemination (3) Marketing costs in marketing channel I of Rp.340.80/kg, on marketing channel II in the amount of Rp. 303.13/kg and in marketi This study aims to (1) Describe cassiavera marketing channels in Kerinci Regency, (2) Analyze the structure, behavior and market performance of cassiavera in Kerinci Regency, (3) Analyze cassiavera marketing efficiency in Kerinci Regency. The study was conducted in Kerinci Regency with a total of 30 respondents. Marketing Channel Description is done by describing several marketing channels. Market Structure Analysis is used with several indicators, namely the number of sellers and buyers, barriers to market entry, the nature of the product, market information. Marketing efficiency analysis is done by analyzing market performance through marketing margins, farmer's share, and profit ratios. The results showed that (1) There were Cassiavera three marketing channels in Kerinci Regency, channel I (Farmer-PPD-PPKec-PPKab-Exporter Company), marketing channel II (Farmer-PPkec-PPKab-Exporter Company), marketing channel III (Farmer-PPKab-Exporter Company), (2) Market Structure leads to oligopic markets, homogeneous product characteristics, high market entry barriers and non-transparent ng channel III Rp. 469.66/kg. Marketing Margin Calculation in each channel shows that the biggest marketing margin in marketing channel III is Rp 1,500.00/kg, in marketing channel I is Rp.1,045.50/kg and in marketing channel III is Rp.1000.00/kg . The profit/cost ratio obtained in marketing channel I was 2.18%, in marketing channel II the profit/cost ratio was 2.23% and the profit/cost ratio in channel III was 2.19%. Farmer's Share in marketing channel I was IDR 67.36%, in marketing channel II was 68.25% and in marketing channel III was 66.15%. From all marketing channels, it is found that marketing channel II is an efficient cassiavera marketing channel.